Pentingnya Literasi Sebagai Pendidikan Karakter dalam Mengatasi Degradasi Moral di Sekolah Dasar - Jamilla Agustin Ummu Sholih; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to explain the importance of literacy as a form of character education in overcoming moral degradation in elementary schools. Moral degradation, a decline in attitudes and behavior in elementary school students, is caused by a lack of instilling a spirit of character in students. There are many cases and problems regarding morals in the surrounding environment. The research method used is a descriptive qualitative approach. Data collection techniques are based on library sources such as journals, articles and books. Then, the results obtained show that literacy activities in elementary schools as a form of character education according to various literature sources can be very useful, especially for overcoming moral degradation in elementary schools. Apart from that, as an Indonesian citizen, you need to have good attitudes and behavior as a form of love for your nation and state